Peran Pejabat Pembuat Akta Tanah dalam Penerbitan Sertifikat Tanah Elektronik - Ni Kadek Wina Surya Adiyanti; Ida Bagus Anggapurana Pidada (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study discusses the role of Land Deed Making Officials (PPAT) in the issuance of Electronic Land Certificates (e-Certificates) in Indonesia, as part of efforts to modernize land administration. The purpose of this research is to understand the contributions and challenges faced by PPAT in the implementation of e-Certificates. The research method used is qualitative descriptive with data collection through in-depth interviews and analysis of official documents. The results of the study show that PPAT has a vital role in maintaining the validity and security of land transactions through the creation of legal land deeds. The implementation of e-Certificates offers a variety of advantages, including higher efficiency, transparency, and better security of land documents through blockchain technology or digital signatures. However, there are several challenges in its implementation, such as the readiness of technological infrastructure, data security, and the limitation of human resources skilled in information technology. Cooperation and coordination between PPAT and the National Land Agency (BPN) is the key to ensuring the success of the issuance of e-Certificates. By understanding the roles and challenges faced by PPAT, this study provides recommendations for improving the process of issuing electronic land certificates and supports the government's efforts to improve more modern and efficient land services in Indonesia.